1995
DOI: 10.1111/j.1439-0329.1995.tb00331.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Gremmeniella abietina isolates from Pinus sylvestris and Pinus contorta in terms of conidial morphology and host colonization

Abstract: Gremmeniella abietina isolates from Pinus contorta in northern Sweden produced, in vitro, shorter conidia with fewer septa compared with isolates from Pinus sylvestris in the southern part of the country. After tnycelial inoculation of shoots with G. abietina isoLites from both host species, the resulting necroses were longer in P. sylvestris than in P. contorta. Keeping seedlings in artificial mild winter clitnate or detaching shoots frotn the seedling before inoculation caused longer necroses. No host specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

1996
1996
2005
2005

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…These types have been named as A and B types or large (LTT) and small (STT) tree types, respectively. Analysis on DNA (Hellgren andHögberg 1995, Hamelin et al 1996) and immunoblotting (Petäistö et al 1996) supported the results of morphological studies. In northern Sweden these types have been shown to infect both Scots pine and lodgepole pine, so that there is a risk of G. abietina spreading from infected lodgepole plantations to Scots pine, and vice versa.…”
Section: Scleroderris Cankermentioning
confidence: 76%
See 1 more Smart Citation
“…These types have been named as A and B types or large (LTT) and small (STT) tree types, respectively. Analysis on DNA (Hellgren andHögberg 1995, Hamelin et al 1996) and immunoblotting (Petäistö et al 1996) supported the results of morphological studies. In northern Sweden these types have been shown to infect both Scots pine and lodgepole pine, so that there is a risk of G. abietina spreading from infected lodgepole plantations to Scots pine, and vice versa.…”
Section: Scleroderris Cankermentioning
confidence: 76%
“…Studies on the spore morphology of G. abietina in northern and southern Finland (Uotila 1983(Uotila , 1990(Uotila , 1992(Uotila , 1993 and Sweden (Hellgren 1995) have revealed that there are two different types of Gremmeniella in the Nordic countries. These types have been named as A and B types or large (LTT) and small (STT) tree types, respectively.…”
Section: Scleroderris Cankermentioning
confidence: 99%
“…One of the most important findings was the lack of obvious differences in the genetic composition between isolates attacking P. sylvestris and those attacking P. contorta. G. abietina isolates from P. sylvestris in southern Sweden and from three P. contorta plantations in one restricted area in northern Sweden differed with respect to conidial measurements and septation, but not with regard to host colonization (HELLGREN 1995). Analogous findings, indicating a lack of host-specificity, were revealed by a recent analysis of RAPD variation of essentially the same material (HELLGREN and HOGBERG 1995), Nor did HAMELIN et al (1995) find any evidence of host-specificity in a survey of European isolates.…”
Section: Overall Genetic Variationmentioning
confidence: 88%
“…Karst.] Then, three biotypes have been distinguished within Europe based on disease symptoms, conidia morphology and using different molecular methods (Uotila 1983(Uotila , 1993Hamelin et al 1993Hamelin et al , 1996Hellgren and Hö gberg 1995;Hellgren 1995;Hantula and Mü ller 1997). causes stem canker and shoot blight on several conifer species (Donaubauer 1972).…”
Section: Introductionmentioning
confidence: 99%
“…In Europe, the EU race has been recognized as being widely distributed throughout Europe on Pinus, Picea and Larix spp. Then, three biotypes have been distinguished within Europe based on disease symptoms, conidia morphology and using different molecular methods (Uotila 1983(Uotila , 1993Hamelin et al 1993Hamelin et al , 1996Hellgren and Hö gberg 1995;Hellgren 1995;Hantula and Mü ller 1997).…”
Section: Introductionmentioning
confidence: 99%